The influence of geology and ore deposit occurrence conditions on dilution indicators of extracted reserves (Rudarsko-geološko-naftni zbornik, 2018)
The development of iron-ore deposits is accompanied by the excavation formation of considerable dimensions in the underground space and to ensure high technical and economic indicators of extraction, especially when developing high-grade iron ore, it is necessary to take into account the nature of the geological structure of the massif on the indicators of their dilution. It is established that when the chambers are worked out on a junction with hanging wall waste, the indices of ore dilution with the adjacent strata are 1.7 times higher than on a junction with the foot wall of the deposit. The tendencies and causes of variability of volume of extracted ore dilution with the adjacent strata in different geological structure parts of the ore deposits are revealed, the ore basin across the pitch is characterized by a general evolving trend of the rock strength of the hanging wall and ore basin angle of incidence decreasing and increasing the thickness of the deposit from the northern side to the southern one. It has been established that the concentration of hanging rocks caving and extracted ore dilution indices is enhanced by changing their morphological composition, reducing the strength and stability of these rocks, reducing the ore basin angle of incidence, and increasing the ore deposit thickness. The obtained results allow us to lay the foundations for optimizing the parameters of the development system and the rational procedure for breaking up ore reserves in the chambers under the changing mining and geological conditions of field development.